Strongyloidiasis--an insight into its global prevalence and management. - Santhosh Puthiyakunnon; Swapna Boddu; Yiji Li; Xiaohong Zhou; Chunmei Wang; Juan Li; Xiaoguang Chen (Public Library of Science (PLoS), 2014)
Strongyloides stercoralis, an intestinal parasitic nematode, infects more than 100 million people worldwide. Strongyloides are unique in their ability to exist as a free-living and autoinfective cycle. Strongyloidiasis can occur without any symptoms or as a potentially fatal hyperinfection or disseminated infection. The most common risk factors for these complications are immunosuppression caused by corticosteroids and infection with human T-lymphotropic virus or human immunodeficiency virus. Even though the diagnosis of strongyloidiasis is improved by advanced instrumentation techniques in isolated and complicated cases of hyperinfection or dissemination, efficient guidelines for screening the population in epidemiological surveys are lacking.In this review, we have discussed various conventional methods for the diagnosis and management of this disease, with an emphasis on recently developed molecular and serological methods that could be implemented to establish guidelines for precise diagnosis of infection in patients and screening in epidemiological surveys. A comprehensive analysis of various cases reported worldwide from different endemic and nonendemic foci of the disease for the last 40 years was evaluated in an effort to delineate the global prevalence of this disease. We also updated the current knowledge of the various clinical spectrum of this parasitic disease, with an emphasis on newer molecular diagnostic methods, treatment, and management of cases in immunosuppressed patients.Strongyloidiasis is considered a neglected tropical disease and is probably an underdiagnosed parasitic disease due to its low parasitic load and uncertain clinical symptoms. Increased infectivity rates in many developed countries and nonendemic regions nearing those in the most prevalent endemic regions of this parasite and the increasing transmission potential to immigrants, travelers, and immunosuppressed populations are indications for initiating an integrated approach towards prompt diagnosis and control of this parasitic disease.